Motivation to Practice in Free Time during the Covid-19 Pandemic - Dinangsit, Dinar; Alif, Muhammad Nur; Sudirjo, Encep (Universitas Pendidikan Indonesia, 2021)
The Covid-19 pandemic that suddenly appeared at the beginning of 2020 spread quickly throughout the world, including in Indonesia. Social restrictions to prevent the transmission of Covid-19 eliminate the essential characteristics of humans and individuals who need to move to maintain their existence as biological and social beings. The effect of inactivity includes a decrease in health quality and an increase in the illness rate. Therefore, this study aimed to examine physically active behavior to fill spare time during restrictions in the Covid-19 pandemic. Related to physical activity behavior from a psychological perspective, motivation to practice in leisure time is seen as a predictor for involvement in physical activity. The participants of this study were Elementary School students aged 10-12 years old, seen as the critical transition stage of physical and psychological development. The number of male and female samples, each consisting of 50 people, were selected through convenience sampling. They were voluntarily willing to be a respondent to answer a self-report process using the motivation to practice in free time scale (MBWL). The construct validity of the scale had met the requirements as well as the internal consistency of each item. The results of the study showed that male students' motivation to practice in their free time was higher than female students.Â